2019
DOI: 10.1007/s00702-019-02112-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of dopamine neurons by xenon against low-level excitotoxic insults is not reproduced by other noble gases

Abstract: Using midbrain cultures, we previously demonstrated that the noble gas xenon is robustly protective for dopamine (DA) neurons exposed to l-trans-pyrrolidine-2,4-dicarboxylate (PDC), an inhibitor of glutamate uptake used to generate sustained, low-level excitotoxic insults. DA cell rescue was observed in conditions where the control atmosphere for cell culture was substituted with a gas mix, comprising the same amount of oxygen (20%) and carbon dioxide (5%) but 75% of xenon instead of nitrogen. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…Xenon's biological effects were studied previously in numerous animal models (rat, dog, rabbit, etc. ), 35−39 bacteria, 40 cancer cells, 41 kidney cells, 42 neurons, 43,44 and human volunteers. 45,46 Although carried out in a different model system, our studies find protein targets that overlap with previously established modes of action for xenon, specifically xenon's ability to inhibit or influence the activity of proteins with ATP-dependent activity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Xenon's biological effects were studied previously in numerous animal models (rat, dog, rabbit, etc. ), 35−39 bacteria, 40 cancer cells, 41 kidney cells, 42 neurons, 43,44 and human volunteers. 45,46 Although carried out in a different model system, our studies find protein targets that overlap with previously established modes of action for xenon, specifically xenon's ability to inhibit or influence the activity of proteins with ATP-dependent activity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Overactivation of NMDA receptors leads to an unpredictable amount of calcium influx that triggers cellular cascades and, ultimately, kills brain cells. Xenon has been proven to exert neuroprotective properties in both in vivo and in vitro models, including HIE in neonates, TBI, stroke, cerebral ischemia following CA, AD, PD, and L-dopa-induced dyskinesia (LID) ( Thoresen et al, 2009 ; Chakkarapani et al, 2010 ; Arola et al, 2013 ; Campos-Pires, 2013 ; Campos-Pires et al, 2015 ; Azzopardi et al, 2016 ; Laitio et al, 2016 ; Lavaur et al, 2016 ; Campos-Pires et al, 2018 ; Campos-Pires et al, 2019 ; Le Nogue et al, 2020 ). The technique of applying moderate hypothermia (33°C–34°C) is widely adopted for the treatment of neonatal asphyxia, becoming a standard strategy in some countries ( Azzopardi et al, 2012 ).…”
Section: Xenonmentioning
confidence: 99%
“…An in vitro study using midbrain cultures found that xenon was a robustly neuroprotective agent for DA neurons ( Lavaur et al, 2017 ). The protective effect of xenon for DA neurons was concentration-dependent, as evidenced by optimal effects at concentrations ranging from 50% to 75% ( Le Nogue et al, 2020 ). These findings pave the way for future clinical studies and shine a light on applications of xenon for AD, PD, and LID.…”
Section: Xenonmentioning
confidence: 99%
See 1 more Smart Citation
“…За несколько десятилетий были получены данные о кардио-, нейро-, нефропротективных свойствах аргона при различных патологических процессах в экспериментальных моделях in vivo и in vitro . Получены новые знания о молекулярных механизмах действия аргона, проведено сравнение защитных эффектов аргона и других благородных газов, в частности, ксенона [37][38][39].…”
Section: Introductionunclassified